Exploring Malaysian landscape practitioner standpoint towards risk definition in landscape architectural project - S. Muthuveeran, Adam Aruldewan; Shahidan, Mohd Fairuz; Hasna, Mohd Fabian; Azmi, Athira; Mustaffa Kamal, Mohd Firdaus; Rasidin, Elly Widiyanty (Human Resource Management Academic Research Society, 2023)
In Malaysia, landscape architectural projects are known for being fast-paced and subjective, making them susceptible to various risks. A project practitioners must comprehensively understand risk perception to manage project risks through a systematic risk management approach effectively. This study aim to define the concept of risk perception from the viewpoint of landscape architecture professionals. The study conducted semi-structured interviews with twenty-four landscape architect professionals in the Klang Valley region of Malaysia. Content and thematic analysis were used to analyze the study's data, which helped identify common themes and patterns in the responses. The study's results reveal that landscape risk perception is deficient, with risks seen as a threat to the project, uncertain, and inevitable. These findings indicate that landscape architecture professionals lack understanding of the potential risks involved in their projects. The study's findings provide valuable insights for project practitioners to evaluate their current risk definition conception and to enable implement the most effective risk management system to manage project risks.